PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 0 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Aminah Aminah; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract The research is begin from the low of the social studies students learning outcomes with an average grade 53,43 while the value of minimum criteria of completeness (KKM) is 65. This research is classroom action research (CAR). That suppose to increase the social studies student learning outcomes at fourth grade of elementary school 008 Sungai Segajah Kecamatan Kubu Rokan Hilir District. The formulation of the research is does the application of cooperative learning model type make a match to increase the students learning outcomes of social student at tree brade of elementary school 008 Sungai Segajah Kecamatan Kubu Rohil district. The data was collected by using observation paper. And god the result by examination I and II. The value before CAR by individual are 16 students that passed with average 65. And in cycle II that passed are students with average passed 70,93. So the improvement of students learning out comes from the bassed score to cycle I increase about 21,65% whereas from based score to cycle II increase about 32,75%. The activity of the teacher in first cycle with average 70,83% and in second cycle about 87,5%. The student is activity in first cycle is average about 62,5% and the scond cycle is everage 83,33%. The result of this research said that the application of cooperative learning model type make a match can increase the social studies students learning outcomes at tree brade of elementary school 008 Sungai Segajah Kecamatan Kubu Rokan Hilir District.Key Word : Kooperative type make a match, The social student achievement